EXPLORING THE UNINTENDED CONSEQUENCES OF MISUSE OF WEGOVY AND OZEMPIC IN WEIGHT MANAGEMENT: A COMPREHENSIVE REVIEW - KUTE, SARTHAK A.; CHOTHAVE, MADHURA S.; ROTE, PRAJAKTA B.; KAPADNIS, ANUPAMA A.; KALE, VAISHNAVI V. (International Journal of Pharmacy and Pharmaceutical Sciences, 2024)
In recent years, Glucagon-Like Peptide-1 (GLP-1) receptor agonists have emerged as promising options for weight management, offering not only glycemic control benefits but also significant reductions in body weight. Among these agents, Wegovy (semaglutide) and Ozempic (semaglutide) have gained attention for their efficacy in promoting weight loss, even in individuals without diabetes. However, the off-label use of these medications for weight management raises several questions and concerns regarding their safety, efficacy, and long-term effects. This comprehensive review aims to explore the complexities of GLP-1 agonists in weight management, focusing on their mechanism of action, clinical evidence, safety profile, dosing considerations, potential interactions, and future directions.